Daily Challenge/Hindrance Demands and Cognitive Wellbeing: A Multilevel Moderated Mediation Model - Chen, Huangen; Wang, Hongyan; Yuan, Mengsha; Xu, Shan (Frontiers in Psychology, 2021)
Based on the challenge-hindrance stressor model, this study explored the mechanism of how challenge/hindrance demands affect cognitive wellbeing on a daily basis. Specifically, we examined the mediating effect of work–family enrichment on the relationship between challenge/hindrance demands and cognitive wellbeing. In addition, we tested the moderating effect of overqualification on the relationship between challenge/hindrance demands and work–family enrichment on a daily basis. Finally, we examined the moderated mediation effect of perceived overqualification in a multilevel model. To capture changes in work–family enrichment and cognitive wellbeing that individuals perceived daily, the experience sampling method was adopted to test our theoretical models. A total of 99 participants from China were involved in this investigation. The results showed that daily challenge demands had a significant positive effect on daily cognitive wellbeing, and daily hindrance demands had a significant negative effect on wellbeing. In addition, daily work–family enrichment mediated the positive relationship between daily challenge demands and daily cognitive wellbeing. Moreover, perceived overqualification moderated the relationship between daily challenge demands and daily cognitive wellbeing in the multilevel model. Finally, a significant moderated mediating effect of this overqualification on the indirect effect of daily work–family enrichment on the relationship between daily challenge demands and daily cognitive wellbeing was observed.